A Rebel in the Labyrinth of Solitude: the Reception of Camus’ Ideology by Octavio Paz (Castilla. Estudios de Literatura, 2013)
Starting from on the contacts Octavio Paz (1914-1998) established with Albert Camus and the philosophical tendency of existentialism in the Paris of the forties, we propose a different approach to his depiction of the pachuco in The Labyrinth of Solitude (1950). We hypothesize that Paz’ perspective should not be interpreted as an autonomous and realistic description but rather as a constituent part of a broader textual unity that can only be understood in its proper philosophical context. We interpret the description of the pachuco as an example of the impact that French existentialism had on Paz’ production at that time. Deepening this insight, we reinterpret the portrayal as a reappraisal of the pachuco as a symbol of how a subversive attitude of rebellion can provide a basis to construct a new Mexican identiy.